Gut bacteria comparison between wild and captive neotropical otters - Laura C Rodríguez-Rey , Johanna Santamaría-Vanegas (Universitas Scientiarum)
The neotropical otter (Lontra longicaudis) is considered a flagship species for the conservation of the ecosystems in which it resides and is currently in a vulnerable state. As a conservation strategy for this species, rehabilitation, breeding, and reintroduction programs of captive individuals have been proposed. However, it is likely that the environment and feeding conditions in captivity result in gut microbial communities that differ from those in wild animals. Gut microbial communities have an important role in the physiological performance of an animal. To determine differences between gut microbial communities of otters in wild and captive living conditions, the structure and diversity of their gut bacterial communities were determined using 16S rDNA molecular markers. Total DNA was isolated from fecal samples of wild animals from the La Vieja River basin and from captive animals in the Cali Zoo. As expected, the gut bacterial communities of captive animals converged to a more similar structure, and their bacterial diversity was significantly lower than that found in wild animals.